Faktor-faktor Penyebab Terjadinya Tindakan Vandalisme di Kantor Arsip Perpustakaan dan Dokumentasi Kota Padang - Barcell, Faramodyta; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper focuses on the factors that cause the occurrence of acts of vandalism at the office of Archives, Library and Documentation Padang. This study aims to reveal: (1) the factors that cause the occurrence of acts of vandalism at the office of Archives, Library and Documentation Padang, (2) the steps that must be done to tackle vandalism librarian to the collection in the Archives, Library and Documentation Padang. Data were collected through observation and interviews with librarians at the Office of Archives, Library and Documentation Padang. analyzing data descriptively. By analyzing the data, it was concluded the following. First, the factors that cause the occurrence of acts of vandalism due to the factor of user and factors of librarians. Factors include lack of awareness of user in using library collections, disappointment user to services librarians, collection of interest and age user mostly teenage boys who are the cause of vandalism in the Archives, Library and Documentation in the city of Padang. While factors include the lack of supervision of the librarian librarians to user and library collections, less specifically rule libraries, librarians are less professional and lack the security of the library. Second, ways of coping with the increasing acts of vandalism that electronic security systems such as the installation of matric sensors, alarm sensors, and CCTV. The socialization user awareness to keep the collection as user education, talk shows, workshops, seminars and training. Keywords: vandalism; library user; librarian